Detección de Staphylococcus aureus en teléfonos móviles de estudiantes de último año de odontología - Vergara Sarmiento, Oscar Fabián (2023)
Objective: The purpose of this study was to detect the incidence of S. aureus on mobile phone screens of last-year dental students using microbiological techniques. Methodology: Descriptive cross-sectional observational study. 92 samples were taken from mobile phone screens, S. aureus was identified by microbiological tests: mannitol fermentation, positive reactions to deoxyribonuclease, catalase and coagulase tests. Results: 16 strains of S. aureus 16/92 (17.4%) were isolated on mobile phone screens. 100% of the strains emerged positive reactions to deoxyribonuclease, catalase and coagulase tests. Conclusions: The presence of S. aureus is evidenced in cell phone screens of senior students’ mobile phones, which represents a risk for the spread of this pathogen.